A study on financial analysis and management issue in Mahkota Medical Centre Melaka / Nurulhuda Mohd Nor - Mohd Nor, Nurulhuda (2011)
This study is about to review, investigate and analyze the financial condition and the management aspect of staffing shortage face by one of private healthcare centre in Melaka, Mahkota Medical Centre Sdn Bhd. Financial condition is the status of a firm's assets, liabilities and equity positions at a specific point in time, often described in a financial statement. While financial analysis means the process of evaluating businesses, projects, budgets and other finance-related entities to determine their suitability for investment. One of the most common ways of analyzing financial data is to calculate ratios from the data such as income statement and balance sheet of a company, to compare against other companies or against the company's own historical performance. For example, return on assets is a common ratio used to determine how efficient a company is at using its assets and as a measure of profitability. This ratio could be calculated for several similar companies and compared as part of a larger analysis. Any company should analyzing and review these ratios every year to ensure that their performance is good and any shortcomings should be taken corrective action. On the other hand, staffing shortage is a shortfall in the number of workers with the skills needed to fill the jobs currently available. A skills shortage may be caused by a lack of education and vocational training, or by wider social and economic factors such as new technological developments. A skills shortage may affect a region, an industry, or a whole country. Skills shortages of this type need to be addressed at national level through effective manpower planning and the development of strategies for adult education and vocational training. An organization may suffer from a skills shortage as a result of poor recruitment and employee retention policies, or through inadequate provision of training and employee development opportunities.